Indigenous Peoples, Poverty and the Role of Social Workers - Suradi Suradi; Soni Akmad Nulhaqim; Nandang Mulyana; Edi Suharto (Asian Social Work Journal, 2019)
Indigenous peoples were placed as second-class citizens, that have fallen behind in all aspects of life than any other citizen. In fact, indigenous people in any country has gained international legal protection through 'the United Nations Declaration the Right of Indigenous People' since 2007. In the entity, within the indigenous peoples, including women and children. The form of response to the declaration, each country develop policies in the form of regulation and followed by action programs targeting indigenous peoples. It has been over 10 years of the declaration proclaimed, but the indigenous peoples still face a lot of problems in the social, cultural, economic, political, legal, land and natural resources; not even the women and their children. This situation requires the presence of a social work profession, in which the role of professional help to acquire rights, improve the quality of life and well-being of indigenous peoples. Keywords: indigenous peoples, poverty, social worker.